Aging and non-native speech perception: A phonetic training study. (1st January 2021) - Tamminen, Henna; Kujala, Teija; Näätänen, Risto; Peltola, Maija S.
Highlights: Seniors show training effects in the most attention demanding perceptual tasks. No training effects in discrimination or neural perception. Experience-based linguistic knowledge benefits the elderly. Abstract: Cognitive decline is evident in the elderly and it affects speech perception and foreign language learning. A listen-and-repeat training with a challenging speech sound contrast was earlier found to be effective in young monolingual adults and even in advanced L2 university students at the attentive and pre-attentive levels. This study investigates foreign language speech perception in the elderly with the same protocol used with the young adults. Training effects were measured with attentive behavioural measures (N = 9) and with electroencephalography measuring the pre-attentive mismatch negativity (MMN) response (N = 10). Training was effective in identification, but not in discrimination and there were no changes in the MMN. The most attention demanding perceptual functions which benefit from experience-based linguistic knowledge were facilitated through training, whereas pre-attentive processing was unaffected. The elderly would probably benefit from different training types compared to younger adults.